Problems of modern interpretation of H. C. Andersen’s literary heritage - Капустян, Інга Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article is dedicated to the study of interpretation of H. C. Andersen in Scandinavian scientific and critical discourseat the beginning of twentieth century. The article deals with the critical and scientific works of literary critics, philosophers and writers. The critics focused on the author’s manner of the creation of artistic images, his authentic simplicity and comprehensiveness of his individual style. The notion of interpretation was considered in the traditional sense and on the account of contemporary literary process, which includes leading literary critics of Scandinavian countries. Particular attention is paid to the writer’s translation into other languages (English, Eastern Slavic, etc.).